The effectiveness of COVID-19 public health campaigns by the Ministry of Health Malaysia: an exploratory study in a university campus / Alis Nerindo, Jamaluddin Jamari and Saodah Wok - Nerindo, Alis; Jamari, Jamaluddin; Wok, Saodah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2021)
In Malaysia, public health campaigns are organized to educate the public about the danger of the COVID-19 pandemic and the government policies to contain a further spread of the pandemic, including the mandatory wearing of face masks in crowded public areas. The campaigns are also aimed at creating awareness among the public of the need to break the pandemic chain. The motto of ‘prevention is better than cure’ forms Malaysia’s basis to strategize, implement, and execute public health campaigns. The aim of this study is to determine the level of knowledge, awareness, perception, attitude, and behavior of International Islamic University Malaysia (IIUM) community towards COVID-19. An online survey was conducted from July 3 to 13, 2020, involving 110 staff and students of IIUM as the respondents of the study. Results showed that the campaigns have been successful as the IIUM community has used the campaigns to be more informed about COVID-19 and more proactive in breaking the pandemic chain, including changing their unhealthy lifestyle, besides being ready to cooperate in observing the Standard Operating Procedures (SOP) implemented by the government as a source of information that educates the public on the pandemic.